Terrestrial Stilling Projected to Continue in the Northern Hemisphere Mid‐Latitudes. Issue 7 (13th July 2022) - Deng, K.; Liu, W.; Azorin‐Molina, C.; Yang, S.; Li, H.; Zhang, G.; Minola, L.; Chen, D.
Abstract: The near‐surface wind speed over land has declined in recent decades, a trend known as terrestrial stilling (TS). However, recent studies have indicated a reversal of the TS during the last decade, triggering renovated interest in the future wind speed changes. This study examines the TS over the Northern Hemisphere (NH) land areas and explores its future changes under Model Inter‐comparison Projection Phase 6 Shared Socioeconomic Pathways (SSP) scenarios. The results show that the NH mid‐latitude TS will likely continue during the whole 21st century under mid‐to‐high greenhouse warmings (SSPs‐245, 370, and 585). Nevertheless, if the world reduces carbon emissions substantially (SSP‐126), the TS will be interrupted and likely reversed after the mid‐21st century. The projected TS shows seasonal differences, with the largest (smallest) decreasing trends of wind speed in boreal summer (winter). Moreover, the TS reversal during the last decade is suggested as a multi‐decadal fluctuation related to the Pacific and Atlantic multi‐decadal oscillations. In addition, this study proposes that increased upper‐air warming in the future climate could play a key role in reducing the NH mid‐latitude surface wind speed. The continuing TS provides strong implications for the near‐surface environment and wind energy development, particularly for countries in the NH mid‐latitudes. Plain Language Summary: The 10‐m wind speed (NWS) is a key parameter in meteorology and climate science, whose changes could affect the natural environment and human society. Previous studies reported that the 10 m wind speed over land had weakened over the past several decades, a phenomenon termed terrestrial stilling (TS). However, recent studies based on observation and reanalyzes showed that the TS started to recover during the last decade, which had caused renewed interest in wind speed changes in the future. This study indicates that the NWS in the Northern Hemisphere (NH) mid‐latitudes will likely continue to weaken during the 21st century forced by increased greenhouse gases. However, if the world cuts carbon emissions substantially, the decline of NWS will be interrupted and reversed after the mid‐21st century. Future changes in NWS show seasonal differences, with the largest (smallest) decreasing trends of NWS in summer (winter). In this study, we propose that elevated upper‐air warmings over the mid‐latitudes could also play a key role in reducing the NWS. This study is useful for understanding the changes in hydrological cycles, air pollution, and wind energy development, particularly for countries in the NH mid‐latitudes. Key Points: Terrestrial stilling (TS) is projected to continue in the Northern Hemisphere mid‐latitudes The stilling‐reversal could be related to the Pacific and Atlantic multi‐decadal oscillations Increased upper‐air warming may favor the TS